Mapping ecosystem service clusters and exploring their driving mechanisms in karst peak-cluster depression regions in China - Zhang, Xuemao; Xie, Binggeng; Zhou, Kaichun; Li, Junhan; Yuan, Chuan; Xiao, Jianyong; Xie, Jing (Ecological indicators, 2024)
•Trade-offs and synergies between ecosystem services were evaluated.•Self-organizing map was used to identify ecosystem services bundles.•Ecosystem service interrelationships are influenced by natural and social factors.•Our findings can form the basis of ecological environmental management policies. Understanding the intricate interrelationships among ecosystem services (ESs) and exploring their driving mechanisms are prerequisites for their efficient management. The southwestern karst region is a typical ecologically fragile area and a crucial component for establishing an ecological security barrier in southern China. We aimed to evaluate the relationship between ESs and the concept of ecosystem service bundles (ESBs) and explore the distribution of ESs and their interrelationships. Using methods, such as Spearman's correlation and spatial autocorrelation analysis, this study focused on the karst peak-cluster depression region in southwestern China to analyse the trade-offs and synergistic effects among 12 ESs. Additionally, this study used the self-organizing map to identify ESBs and used the Random Forest model to explore the potential driving factors influencing the distribution patterns of ESs. The results indicated a spatial clustering effect among the 12 ESs, whereby provisioning and cultural services had the most significant clustering effect (Moran's I > 0.8). A total of 25 pairs of ESs exhibited synergistic effects, and 31 pairs showed trade-off effects. Food production showed a trade-off with both regulatory and supporting services, whereas ESs within the same category tended to exhibit synergistic effects. The distribution and interrelationships of ESs are influenced by natural and social factors, such as climate, topography, and human activities, resulting in the formation of six ESBs. This study enriches the understanding of the relationship of ESs and will contribute to the coordinated development of resources and the environment in the karst peak-cluster depression region of southwestern China.